2018
DOI: 10.4236/oja.2018.83004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wood Condition on Sound Wave Propagation

Abstract: This experiment aims to study the effects and modifications that occurred on acoustic signal harmonics when travelling through wood. The experiment measured the output amplitudes and frequencies of the travelling signals and compared them with the original input signal. The factors under investigation in this experiment included: wood type, wood moisture content (MC), input signal frequencies, signal travelling distance and wood condition (wood with/without cracks). The experiment findings demonstrated that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…It was also demonstrated that the signals detected by sensors S1 and S2 had a higher frequency nature (100 ~ 150 kHz) that better correlated with the damping behavior and viscoelastic properties of wood. This is consistent with the general statement that higher signal frequency is usually correlated with a higher attenuation rate [64]. On the other hand, the signals detected from sensors S3 and S4 have a lower frequency nature (30 ~ 50 kHz) and were less sensitive to the viscous properties of wood.…”
Section: Eventsupporting
confidence: 90%
“…It was also demonstrated that the signals detected by sensors S1 and S2 had a higher frequency nature (100 ~ 150 kHz) that better correlated with the damping behavior and viscoelastic properties of wood. This is consistent with the general statement that higher signal frequency is usually correlated with a higher attenuation rate [64]. On the other hand, the signals detected from sensors S3 and S4 have a lower frequency nature (30 ~ 50 kHz) and were less sensitive to the viscous properties of wood.…”
Section: Eventsupporting
confidence: 90%
“…Using appropriate mathematical models, the complex permittivity is then calculated from the measured impedance or admittance. DS can be applied across an extensive frequency range, from very low frequencies in the millihertz (mHz) range to extremely high frequencies in the terahertz (THz) range [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation rate of AE energy showed a significant linear relationship with the increase of MC, indicating that the change of MC had a significant influence on the propagation speed and energy of wood AE signal. El-Hadad et al 16 studied the effect of wood type, input signal frequency, signal transmission distance and wood health condition on AE signals. Ding et al 17 explored the fracture process of wood using information entropy and showed that the energy release of wood during fracture was stochastic in nature.…”
Section: Introductionmentioning
confidence: 99%